Structure of the c-Ki-ras gene in a rat fibrosarcoma induced by 1,8-dinitropyrene. - Tahira, T (1986)
Restriction enzyme maps were made of the region around exons 1 and 2 of activated c-Ki-ras of a fibrosarcoma (1,8-DNP2) induced in a rat by 1,8-dinitropyrene. Nucleotide sequence analysis revealed that activated c-Ki-ras shows a G----T transversion in codon 12 and consequently encodes cysteine instead of glycine in normal rat c-Ki-ras.